Simultaneous removal of mixed pesticides and natural organic matter from surface waters by nitric and chlorosulfonic acid functionalized powdered activated carbon - Aykut-Senel, Betul; Ozgur, Cihan; Bakirdere, Sezgin; Kaplan-Bekaroglu, Sehnaz Sule; Ates, Nuray (WILEY, 2024)
BACKGROUND: Several studies have addressed the adsorption of pesticides such as alachlor, acetochlor, metolachlor and fenthion from water and wastewater, yet the interaction of these compounds with natural organic matter (NOM) complicates their effective removal owing to competitive adsorption effects. This study aims to fill this gap by exploring the efficacy of nitric acid and chlorosulfonic acid-modified activated carbons (ACs) in removing both pesticides and NOM under realistic environmental conditions. RESULTS: Modifications using nitric acid and chlorosulfonic acid significantly improved the pesticide removal capabilities of Norit SX F Cat (AC1) adsorbents. While both the original and chlorosulfonic acid-modified adsorbents showed comparable efficacy in pesticide removal, nitric acid-modified AC Puriss (AC2) adsorbents were less effective. Remarkably, a 100 mg L-1 dose of both original and modified powdered ACs (PACs) removed >98% of all four pesticides from water samples. Additionally, a lower 25 mg L-1 dose effectively achieved similar removal rates, demonstrating their utility as feasible options for water treatment. CONCLUSION: Modifying PACs with nitric acid and chlorosulfonic acid has been proven to enhance their structural and adsorptive properties significantly. These modifications led to improved pesticide removal efficiencies, particularly with the chlorosulfonic acid-modified PACs, which demonstrated superior performance in adsorption tests. The study also highlighted the competitive adsorption posed by low-molecular-weight organic substances in water, which compete with pesticides for active adsorption sites. (c) 2024 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).
Keywords: adsorption; chlorosulfonic acid; chemical modification; natural organic matter; pesticide; powdered activated carbon; MICROPOLLUTANT ADSORPTION; AQUEOUS-SOLUTIONS; DRINKING-WATER; WASTE-WATER; SIZE; NOM; PERFORMANCE; ACETOCHLOR; EXCHANGE; PAC; Biotechnology & Applied Microbiology; Chemistry; Engineering